Efficient Agrobacterium tumefaciens-mediated transformation system of Diaporthe caulivora - Montoya, Marina Rosa; Massa, Gabriela Alejandra; Colabelli, Mabel Noemí; Ridao, Azucena (Elsevier, 2021)
This is the first report describing the genetic transformation of Diaporthe caulivora, the soybean stem canker fungus. A simple and 100% efficient protocol of Agrobacterium tumefaciens-mediated transformation used mycelium as starting material and the hygromycin B resistance and green fluorescent protein (GFP) as a selection and reporter agents, respectively. All transgenic isolates were mitotically stable in two independent experiments and polymerase chain reaction with hygromycin B resistance primers confirmed successful T-DNA integration into the fungal genome. Plant-fungus interaction studies, including pathogenicity, latency, and endophytism, as well as further studies of random and targeted mutagenesis will be possible with GFP-expressing isolates of D. caulivora and other species in the Diaporthe / Phomopsis complex.